Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Three different problem I got:

1.. $xu_x+2x^2u_y-u=x^2e^x$ and $u(x,x^2+x)=xe^x+x^2$

2.. $yu_{xx}+(x+y)u_{xy}+xu_{yy}=0, \quad x\neq y$

3.. $(y+xu)u_x+(x+yu)u_y=u^2-1$

Couldnt even start. Could you at least give me a hint? thanks.


at 2. from $B^2-AC=\frac {(x-y)^2}4>0 $ so the equation is hyperbolic. so we can write its cononical forms. is it true?

edit2: for the first one :

by taking $\eta=x^2-y$ and $\xi=x$ I found $u(x,y)=xe^x+x(-x+1-e^{-x})$ for the second one :

I took $\xi=\frac{x^2-y^2}{2}$ and $\eta=x-y$ and found $u(x,y)=\frac {f^*(\frac{x^2-y^2}{2})}{x-y}+g(x-y)$

edit 3:----------------------

1-) $\frac ba=\frac {2x^2}{x}=2x=\frac {dy}{dx}$

$x^2-y=c$, $\eta =x^2-y$ and $\xi =x$

$u_x=w_{\xi}+w_{\eta}2x$ and $ u_y=-w_{\eta}$

$\xi(w_{\xi}+w_{\eta}2\xi)-2\xi ^2w_{\xi}-w=\xi^2e^\xi $

$w_{\xi}-\frac w \xi=e^\xi$ multiplying by $\frac 1\xi$

$\frac{d(w\frac 1\xi)}{d\xi}=e^\xi$

so we got $w=\xi e^\xi+g(\eta)$


and $u(x,x^2+x)=xe^x+x^2 =xe^x+g(x^2-x^2-x)$

$g(-x)=x^2$, $g(x)=x^2$ so the $u(x,y)=xe^x+x^2$


3)$\frac {\frac{dx}{dt}}{y+ux}=\frac {\frac{dy}{dt}}{x+yu}=\frac {\frac{du}{dt}}{u^2-1}$

$\frac {\frac{dx}{dt}-\frac{dy}{dt}}{y+ux-x-yu}=\frac {\frac{du}{dt}}{u^2-1}$

$\frac {\frac{dx}{dt}-\frac{dy}{dt}}{(1-u)(y-x)}=\frac {\frac{du}{dt}}{u^2-1}$

$\frac {\frac{d(x-y)}{dt}}{y-x}=\frac {\frac{du}{dt}}{u+1}$

$ln(u+1)+ln(x-y)=c_1$------------------- (1) we got one independent solution we need another

$\frac {\frac{dx}{dt}+\frac{dy}{dt}}{y+ux+x+yu}=\frac {\frac{du}{dt}}{u^2-1}$

$\frac {\frac{dx}{dt}+\frac{dy}{dt}}{(1+u)(x+y)}=\frac {\frac{du}{dt}}{u^2-1}$

$\frac {\frac{d(x+y)}{dt}}{x+y}=\frac {\frac{du}{dt}}{u-1}$


from (1) and (2) which form is $h(x,y,u)=c_1$ and $j(x,y,u)=c_2$

general solution would be in $j(x,y,u)=F(h(x,y,u))$ Where F is an arbitrary.

so $ln(u-1)-ln(x+y)=F(ln(u+1)+ln(x-y))$

share|cite|improve this question
I notice you have asked 45 questions, and many people have given answers, but you have only voted up 7 answers. Be sure to show appreciation of people who help you by voting up their answers. Thanks! – Matthew Conroy May 22 '14 at 23:24
@MatthewConroy I didnt notice :) I always accept answers as soon as possible but didnt know upvoting was important so my bad then – lyme May 22 '14 at 23:30
Your first question is very odd. Why both $x$ and $x'$ exist? – doraemonpaul May 23 '14 at 22:02
@doraemonpaul fixed. I was in a hurry. sorry – lyme May 25 '14 at 21:01
up vote 3 down vote accepted

Some hints:

  • First problem: 1st order linear PDE, use the method of characteristics and then apply the "boundary" condition. Edit: note that your solution doesn't satisfy nor the equation nor the "boundary condition". The characteristic equations are given by: $$ \frac{\mathrm{d} x}{x} = \frac{\mathrm{d} y}{2 x^2} = \frac{\mathrm{d} u}{u + x^2 e^x},$$ which from the first equality yields: $$ y - x^2 = \text{constant} \equiv \eta ,$$ which is the characteristic of the PDE. The remaining equation, which comes up from the equality of the first and third terms is a 1st order linear ODE for $u$ as a function of $x$: $$ \frac{\mathrm{d} u}{ \mathrm{d} x} = \frac{u}{x} + x e^x , $$ whose solution (use an integrating factor) is given by $u(x,y) = x \, ( e^x + C)$, being $C$ a constant of integration. Put $C = C(\eta(x,y))$ in order to get the complete solution.

  • Second problem: 2nd oder linear PDE, use the method of characteristics knowing that for $x - y \neq 0$ the equation is hyperbolic but parabolic when $x = y$ (I notice now that you are told $x \neq y$).

  • Third problem: 1st order non-linear PDE, use the Lagrange-Charpit equations, which are a generalization of the characteristics. Edit: this method reads: $$ \frac{\mathrm{d}x}{F_p} = \frac{\mathrm{d}y}{F_p} = \frac{\mathrm{d}u}{p F_p + q F_q} = - \frac{\mathrm{d} p}{ F_x + p F_u} = - \frac{\mathrm{d} q}{F_y + q F_u} , $$ where $F(x,y,u;p,q) = (y+xu)u_x + (x+yu) u_y-u^2 -1 $ and subindices denote partial differentiation with respect the subscript.


share|cite|improve this answer
thanks. I edited my answer but got problem with third. Could you give a link of example of this method – lyme May 26 '14 at 21:31
Of course. Give me some minutes. – Dmoreno May 26 '14 at 21:32
I fixed my answer. I guess first one is true now. I tried something at the third one which I'm not sure if it is true. Can you check again please – lyme May 27 '14 at 10:56




Follow the method in

$\dfrac{dx}{dt}=1$ , letting $x(0)=0$ , we have $x=t$

$\dfrac{dy}{dt}=2x=2t$ , letting $y(0)=y_0$ , we have $y=t^2+y_0=x^2+y_0$

$\dfrac{du}{dt}=\dfrac{u}{x}+xe^x=\dfrac{u}{t}+te^t$ , we have $u=te^t+tf(y_0)=xe^x+xf(y-x^2)$

$u(x,x^2+x)=xe^x+x^2$ :



$\therefore u(x,y)=xe^x+x(y-x^2)=xe^x-x^3+xy$

2.. Solving $yu_{xx}+(x+y)u_{xy}+xu_{yy}=0$

3.. :How to find the general solution of $(y+ux)u_x+(x+yu)u_y=u^2-1$?

share|cite|improve this answer
Could you explain how did you find $u=te^t+tf(y_0)$ – lyme Jun 1 '14 at 12:43
isnt it $u(t)=te^t+ct$ but $u(0)=0=f(y_0)$? – lyme Jun 1 '14 at 15:21

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.